Tanggung Jawab Etis Komunikasi Berdasarkan Etika dalam Berkomunikasi di Era Globalisasi dan Industri - Filza Frilatia Bahri; Nabila Maharani; Intan Safitri; Ramayati Ramayati; Siti Auliza; Novendra Hariyadi Ritonga (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
Communication as a scientific discipline evolves in tandem with the progress of time and technology, becoming essential in human life. In the era of globalization and modern industry, the field of communication science is crucial to understanding the impact of information technology, social media, and the dynamics of human relationships. Ethical responsibility in communication involves principles such as honesty, integrity, respect, and empathy. Scientific communication skills assist in effectively conveying messages, while mastering information technology plays a vital role in meeting information needs amidst global competition and social changes. Literature studies help elaborate on the basic concepts of science, the evolution of communication science, and the impact of globalization on communication. Therefore, this research outlines ethical responsibilities and the relevance of communication science in facing challenges and opportunities in the contemporary era.